Análise do potencial eólico produzido pelo deslocamento de ar durante a passagem de veículos em uma rodovia federal : um estudo de caso na BR 101 no Estado da Paraíba - Mesquita, Emmanuelle Carneiro de (2024)
Given the increase in demand for energy, there is a need to use more renewable energy sources that allow a sustainable supply, contributing to the mitigation of environmental impacts. Wind energy is produced from the force of winds and is considered a source of clean energy, as it is generated, it can be used in an alternative matrix using new technologies for such production. There are wind generators in various scales and shapes and unconventional prototype options have been proposed. Among them, there is the small wind turbine that transforms the air flow generated by vehicles traveling on the highway into electricity, becoming a sustainable source for infrastructure and can be used for small loads on the main networks. This dissertation analyzed the wind speed generated by the passage of vehicles on Rodovia BR 101, km 101, in the section of the State of Paraíba. Highway wind energy potential originating from moving vehicles can reach wind speeds of up to 11 m/s depending on the speed, intensity and size of the vehicle. The speed was estimated by digital anemometers installed on the sides of the Highway, which recorded the speed at different heights and distances and varying angles. The results obtained under the climatic conditions recorded an efficient and satisfactory average for small-scale energy production. The speeds recorded by the on-site anemometer compared to those recorded by the INMET meteorological station were higher, confirming that the wind wakes created by the movement of the vehicle on the road contribute considerably to the increase in speed. Based on the potential wind speeds and height of the experimental apparatus, five types of small commercial wind turbines that can rotate at low speed were selected. Among them, the ENB-500W VAWT and ENB-300W-HQS VAWT models stood out, presenting superior performance than the others. Finally, given all the data collection, it proved that capturing energy from the highway is something promising, an alternative for generating sustainable energy, offering benefits such as less polluting, improvement in human health, longterm savings, application and incorporation into the energy development of the public system, benefiting society.